ANALYSIS OF THE CONSISTENCY OF PERFORMANCE WITH CHANGES IN THE RANKINGS OF MUTUALS FUNDS PERFORMANCE AT B.R.V.M - Mame Abdou DIOP; Mor Welle DIOP; Mamadou DIOUF; Gnilane FAYE (Revue Internationale du Chercheur, 2025)
Fonds Communs de Placement (FCPs) play a key role in portfolio diversification in West Africa via the BRVM. Our case study focuses on analysing the evolution of FCP performance over the period 2017-2021, with 23 funds in order to identify managers capable of maintaining or improving their performance. Spearman and Wilcoxon statistical tests were used to assess performance persistence. FCP data were extracted from BRVM reports, cleaned and missing values imputed. Only FCPs with continuous five-year data were retained. The results indicate high variability and instability in performance, with cycles of positive and negative persistence limited to certain periods. However, Kendall's test revealed an absence of significant persistence over the entire period studied. The results are limited by the period and the availability of data, and major economic shocks have not been taken into account. Further econometric and qualitative analyses, as well as comparisons with other markets, would be useful. In conclusion, mutual fund managers face difficulties in maintaining persistent performance, and the study opens up prospects for more in-depth future research.